Female preference and male nuptial colouration in the freshwater fish Gobiomorphus breviceps: geographic variation among populations - Hamilton, William J.; Poulin, Robert (Canadian journal of zoology, 1999)
Geographic variation in the strength or direction of sexual selection acting on different populations has been documented before but has not been the subject of intense study. We examine covariation among sexually selected traits and environmental factors for five stream populations of a small New Zealand freshwater fish, the upland bully, Gobiomorphus breviceps (Eleotridae). Levels of infection by a trematode parasite and some aspects of female behaviour and male colouration varied significantly among populations. Among individual fish we found that female mate choice behaviours and male colouration did not correlate similarly with other traits, or with parasite load, in the different populations studied. We also determined whether average population values correlated among the different stream populations. Whereas environmental factors such as water clarity and substrate colouration appeared to be unimportant, average parasite load correlated with some components of male colouration, and female preferences appeared to be correlated with male colouration. These results illustrate both the variability among populations that prevents results obtained from one population from being generalized to the entire species, and the plasticity of sexually selected traits in relation to local conditions.